2021
DOI: 10.1177/03635465211028990
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Graft Rupture Rates After Combined ACL and Anterolateral Ligament Reconstruction Versus Isolated ACL Reconstruction: A Matched-Pair Analysis From the SANTI Study Group

Abstract: Background: Clinical studies have demonstrated significant advantages of combined anterior cruciate ligament and anterolateral ligament reconstruction (ACL+ALLR) over isolated ACL reconstruction (ACLR) with respect to reduced graft rupture rates, a lower risk of reoperation for secondary meniscectomy, improved knee stability, and higher rates of return to sports. However, no long-term studies exist. Purpose/Hypothesis: The purpose of this study was to compare the outcomes of isolated ACLR versus ACL+ALLR at lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 44 publications
1
55
0
1
Order By: Relevance
“…Similarly, the SANTI study group compared outcomes between isolated autograft ACLR to combined autograft ACLR with ALL procedure. 118 Findings from this prospective cohort study of 270 patients showed statistically better ACL graft survivorship in the group who underwent ACLR with ALL (96.5% vs 82.6%; p =0.0027). Additionally, at 108 months, those who had concurrent ALL with primary ACLR had at least 2.5-times reduced graft failure rates.…”
Section: Lateral Extra-articular Proceduresmentioning
confidence: 79%
“…Similarly, the SANTI study group compared outcomes between isolated autograft ACLR to combined autograft ACLR with ALL procedure. 118 Findings from this prospective cohort study of 270 patients showed statistically better ACL graft survivorship in the group who underwent ACLR with ALL (96.5% vs 82.6%; p =0.0027). Additionally, at 108 months, those who had concurrent ALL with primary ACLR had at least 2.5-times reduced graft failure rates.…”
Section: Lateral Extra-articular Proceduresmentioning
confidence: 79%
“…Indeed, the increasing body of evidence demonstrating the advantages of adding a LEAP to an ACLR, in particular, in reducing graft failure, means it is important to get it right the first time and avoid any secondary surgery. 3 , 7 Getgood et al. 3 reported a 2% rate of difficulties with the lateral extra-articular tenodesis at the time of surgery and a 3% rate of hardware removal postoperatively in the STABILITY trial.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Clinical studies have established meaningful advantages of combining an ACLR with a LEAP, including reducing ACLR graft rupture rates, protecting medial meniscal repairs, and improving outcomes in high-risk groups, including revision ACLRs, chronic ACL injuries, and patients with hyperlaxity. 3 , 4 , 5 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…The benefit of this step is still debated in primary ACL reconstruction; however, numerous recently published articles have demonstrated its utility in decreasing graft failure rates and protecting the meniscus suture. 7 , 8 , 9 Consequently, it seems relevant to perform an ALL reconstruction in selected patients (major rotatory instability, constitutional hyperlaxity, high-demand athletes, or patients under 18 years old) ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%